PENGAWASAN PENGELOLAAN ADMINISTRASI GURU DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN DI SMPN 3 TARUMAJAYA KABUPATEN BEKASI - Hapiz; Hardian, Dafyar Eliadi; Mardisentosa, Bambang (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the role of supervision in teacher administration management and its impact on improving the quality of education. Well-organized administration plays a crucial role in supporting the effectiveness of the learning process and achieving educational goals in schools. The research method used was qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation involving principals, teachers, and school supervisors. The results indicate that systematic and continuous supervision can increase compliance with educational regulations, improve teaching effectiveness, and enhance teacher discipline. However, obstacles remain in the implementation of supervision, such as a shortage of supervisors, limited supporting facilities, and a suboptimal understanding of administrative policies. Based on these findings, more effective supervision strategies are needed, such as the use of digital technology for administrative record-keeping, increasing the capacity of supervisors, and implementing a performance-based evaluation system. Thus, supervision of teacher administration management can be more optimal in supporting the improvement of educational quality in schools. Keywords: Supervision, Teacher Administration, Education Quality, Schools.